Insights from Washington State’s COVID-19 Response: A Mixed-Methods Evaluation of WIC Remote Services and Expanded Food Options Using the RE-AIM Framework - Morris, Evelyn J.; Quinn, Emilee L.; Rose, Chelsea M.; Spiker, Marie; O’Leary, Jean; Otten, Jennifer J. (Journal of the Academy of Nutrition and Dietetics, 2022)
In response to the COVID-19 pandemic, Washington State’s Supplemental Nutrition Program for Women, Infants, and Children (WA WIC) adopted federal waivers to transition to remote service delivery for certification and education appointments. WA WIC also expanded the approved food list without using federal waivers, adding more than 600 new items to offset challenges participants experienced accessing foods in stores. This study aimed to assess the reach and effectiveness of the programmatic changes instituted by WA WIC during the COVID-19 pandemic; the processes, facilitators, and challenges involved in their implementation; and considerations for their continuation in the future. A mixed-methods design, guided by the RE-AIM framework, including virtual, semi-structured focus groups and interviews with WA WIC staff and participants, and quantitative programmatic data from WIC agencies across the state. This study included data from 52 state and local WIC staff and 40 WIC participants across the state of Washington and from various WA WIC programmatic records (2017-2021). The research team collected data and conducted analyses between January 2021 and August 2021. An inductive thematic analysis approach with Dedoose software was used to code qualitative data, generate themes, and interpret qualitative data. Descriptive statistics were calculated for quantitative programmatic data, including total participant count, percent increase and decrease in participation, percent of food benefits redeemed monthly, and appointment completion rates. All WA WIC participants (n = 125,279 in May 2020) experienced the programmatic changes. Participation increased by 2% from March to December 2020 after WA WIC adopted programmatic changes in response to the COVID-19 pandemic. Certification and nutrition education completion rates increased by 5% and 18% in a comparison of June 2019 with June 2020. Food benefit redemption also increased immediately after the food list was expanded in April 2020. Staff and participants were highly satisfied with remote service delivery, predominantly via the phone, and participants appreciated the expanded food options. Staff and participants want a remote service option to continue and suggested various changes to improve service quality. Participation in WIC and appointment completion rates increased after WA WIC implemented service changes in response to the COVID-19 pandemic. Staff and participants were highly satisfied with remote services, and both desire a continued hybrid model of remote and in-person WIC appointments. Some of the suggested changes to WIC, especially the continuation of remote services, would require federal policy change, and others could be implemented under existing federal regulations.